Association between Serum Trace Elements Levels, Steroid Concentrations, and Reproductive Disorders in Ewes and Does - Derar Derar; Ahmed Ali; Tariq Almundarij; Essam Abd-Elmoniem; Tamim Alhassun; Moustafa Zeitoun (Veterinary Medicine International)
This study aimed to investigate the association of different reproductive disorders with the status of serum trace elements and steroid hormones in ewes and goats. This study included 131 barren and 11 fertile (control) ewes and 94 barren and 9 fertile (control) goats. Animals were examined gynecologically for reproductive soundness. The animals were bled, and their serum was harvested and assayed for manganese (Mn), selenium (Se), iron (Fe), zinc (Zn), estrogen (E2), and progesterone (P4) levels. The results showed that genital affections were associated with significant changes in serum Se (P=0.001), Fe (P=0.008), and Zn (P=0.01) levels in ewes, as well as Mn (P=0.01) levels in goats. Ewes and goats with cystic ovaries had higher serum Se, Fe, and Zn levels (P=0.0001) than ewes with uterine affections, ovarian inactivity, and controls. Ovarian inactivity was linked to low Se levels in ewes and low Se and Zn levels in goats (P=0.05). Ewes and goats with estrogen-dominant reproductive disorders had higher Se (P=0.01), Fe (P=0.03), and Zn (P=0.01) compared with the control group. Se (P=0.02) and Zn (P=0.05) were lower in ewes and goats affected with P4-dominant genital disorders compared with the control group. It can be concluded that the reproductive disorders are associated with changes in the level of trace elements in blood of ewes and goats. There is a reciprocal relationship between the levels of estrogen and progesterone with those of the trace elements in serum of ewes and goats.